Analisis Kebijakan Moneter Dalam Mengendalikan Inflasi Di Indonesia - Rosenta Febri Mutiara Sinaga; Muhammad Yusuf; Arwansyah (Jurnal Penelitian Ekonomi Akuntansi, 2025)
This study aims to analyze the impact of monetary policy on inflation in Indonesia by examining five independent variables: money supply, interest rates, exchange rates, Gross Domestic Product (GDP), and geopolitical instability from 1990 to 2023. A quantitative research approach was employed using annual time series data and descriptive analysis to observe relevant macroeconomic trends. The results indicate that money supply and exchange rates have a significant long-term effect on inflation, while interest rates and GDP show fluctuating contributions depending on prevailing economic conditions. Geopolitical instability also contributes to inflationary pressure, particularly during global crises and energy price shocks. These findings suggest that the effectiveness of monetary policy is strongly influenced by its responsiveness to both external and domestic dynamics, and the importance of maintaining a balance between price stability and sustainable economic growth.